Double-sided adhesive sheet with liner
Patent Information
- Application Number
- JP2023503374
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-05
- Filing Date
- 2021-11-01
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-11-01
Smart Images

Figure 0007652880000002 
Figure 0007652880000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a liner-attached double-sided pressure-sensitive adhesive sheet. [Background technology]
[0002] Conventionally, when processing a specific member (e.g., electronic components, materials for electronic components, optical components, etc.), the member is temporarily fixed to an adhesive sheet. For example, a member such as an electronic component is fixed on a specific base via a double-sided adhesive sheet, and the member is processed (e.g., resin sealing, cutting, cutting, polishing, etching, printing, etc.), and after processing, the processed product is peeled off from the base.
[0003] In processing the above-mentioned members, the members may be pressurized, as typified by resin sealing, cutting, circuit formation, etc. When the members are pressurized in this manner, uniformity of the pressurization is often required. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-201452 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made to solve the above-mentioned problems in the conventional art, and an object of the present invention is to provide a double-sided pressure-sensitive adhesive sheet that can be used as a temporary fixing material during component processing, and that can increase the uniformity of pressure when pressure is applied to the component. [Means for solving the problem]
[0006] The liner-attached double-sided pressure-sensitive adhesive sheet of the present invention comprises, in this order, a first liner, a first pressure-sensitive adhesive layer, a substrate, a second pressure-sensitive adhesive layer, and a second liner, the second pressure-sensitive adhesive layer containing heat-expandable microspheres, the arithmetic surface roughness Ra of the surface of the first liner facing the first pressure-sensitive adhesive layer being 1 nm to 100 nm, the arithmetic surface roughness Ra of the surface of the second liner facing the second pressure-sensitive adhesive layer being 1 nm to 100 nm, the maximum height Rz of the surface of the first liner facing the first pressure-sensitive adhesive layer being 5 nm to 1000 nm, and the maximum height Rz of the surface of the second liner facing the second pressure-sensitive adhesive layer being 5 nm to 1000 nm. In one embodiment, the heat-expandable microspheres have a volume cumulative particle size D50 of 5 μm to 30 μm. In one embodiment, the heat-expandable microspheres have a volume cumulative particle size D80 of 10 μm to 50 μm. In one embodiment, the product of the cube of the thickness of the substrate and the elastic modulus of the substrate is 1×10 -7 ( N m )~1×10 -2 ( N m ). In one embodiment, the first pressure-sensitive adhesive layer is made of a pressure-sensitive adhesive containing a base polymer, and the base polymer has a glass transition temperature of -50°C to 0°C. In one embodiment, the liner-attached double-sided pressure-sensitive adhesive sheet is used as a sheet for temporarily fixing a semiconductor chip during the manufacture of a CSP (Chip Size / Scale Package). In one embodiment, the liner-attached double-sided pressure-sensitive adhesive sheet is used as a sheet for temporarily fixing a semiconductor chip during the manufacture of a WLP (Wafer Level Package). In one embodiment, the semiconductor chip is pressurized. Effect of the Invention
[0007] According to the present invention, it is possible to provide a double-sided pressure-sensitive adhesive sheet that can be used as a temporary fixing material during component processing, and that can increase the uniformity of pressure when pressure is applied to the component. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view of a liner-attached double-sided PSA sheet according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] A. Overview of double-sided adhesive sheets with liner FIG. 1 is a schematic cross-sectional view of a liner-attached double-sided pressure-sensitive adhesive sheet according to one embodiment of the present invention. The liner-attached double-sided pressure-sensitive adhesive sheet 100 includes, in this order, a first liner 10, a first pressure-sensitive adhesive layer 21, a substrate 22, a second pressure-sensitive adhesive layer 23, and a second liner 30. The first pressure-sensitive adhesive layer 21, the substrate 22, and the second pressure-sensitive adhesive layer 23 constitute a double-sided pressure-sensitive adhesive sheet 20. The arithmetic surface roughness Ra of the surface of the first liner 10 facing the first pressure-sensitive adhesive layer 21 is 1 nm to 100 nm. The arithmetic surface roughness Ra of the surface of the second liner 30 facing the second pressure-sensitive adhesive layer 23 is 1 nm to 100 nm. The maximum height Rz of the surface of the first liner 10 facing the first pressure-sensitive adhesive layer 21 is 5 nm to 1000 nm. The maximum height Rz of the surface of the second liner 30 facing the second pressure-sensitive adhesive layer 23 is 5 nm to 1000 nm.
[0010] The double-sided pressure-sensitive adhesive sheet 20 is composed of the first pressure-sensitive adhesive layer 21, the substrate 22, and the second pressure-sensitive adhesive layer 23. The double-sided pressure-sensitive adhesive sheet 20 may further include any other appropriate layers as long as the effects of the present invention can be obtained. For example, an undercoat layer may be disposed between the second pressure-sensitive adhesive layer and the substrate.
[0011] The double-sided pressure-sensitive adhesive sheet can be used as a temporary fixing material when a member such as an electronic component is placed on the first pressure-sensitive adhesive layer and processed. In the present invention, the surface state of the first liner is specified as described above, thereby forming a first pressure-sensitive adhesive layer having excellent surface smoothness. By using such a double-sided pressure-sensitive adhesive sheet, when a member is pressed on the double-sided pressure-sensitive adhesive sheet, the uniformity of the pressurization can be improved. Furthermore, by specifying the surface state of the second liner as described above, the smoothness of the surface of the first pressure-sensitive adhesive layer (the surface opposite to the substrate) and the uniformity of pressurization with respect to the member to be pressed are improved.
[0012] The second pressure-sensitive adhesive layer contains heat-expandable microspheres. When the pressure-sensitive adhesive layer containing heat-expandable microspheres is heated, the heat-expandable microspheres expand or foam, causing unevenness on the adhesive surface, resulting in a decrease or loss of adhesive strength.
[0013] In one embodiment, when the liner-attached double-sided pressure-sensitive adhesive sheet is used, the first liner is peeled off first. More specifically, the liner-attached double-sided pressure-sensitive adhesive sheet can be used by first peeling off the first liner, attaching a workpiece (e.g., electronic components) to the exposed adhesive surface (e.g., the surface of the first pressure-sensitive adhesive layer), and then peeling off the second liner, and attaching the surface of the second pressure-sensitive adhesive layer to another adherend (e.g., a base). In such an embodiment, the adherend (e.g., electronic components) is temporarily fixed to the base via the double-sided pressure-sensitive adhesive sheet; the adherend is subjected to a predetermined processing; and then the adhesive strength of the second pressure-sensitive adhesive layer is reduced by heating, and the double-sided pressure-sensitive adhesive sheet with the adherend is peeled off from the base.
[0014] B. First liner, second liner Typically, the first liner and the second liner include a liner substrate and a release treatment layer disposed on at least one side of the liner substrate. The first liner and the second liner are disposed so that the release treatment layer faces the double-sided pressure-sensitive adhesive sheet. The first liner and the second liner may have the same configuration or different configurations.
[0015] As described above, the arithmetic surface roughness Ra of the surface of the first liner facing the first pressure-sensitive adhesive layer is 1 nm to 100 nm. The arithmetic surface roughness Ra of the surface of the first liner facing the first pressure-sensitive adhesive layer is preferably 1 nm to 60 nm, more preferably 1 nm to 45 nm, even more preferably 15 nm to 45 nm, and particularly preferably 15 nm to 35 nm. Within such a range, the effects of the present invention are prominent. The arithmetic surface roughness Ra can be measured in accordance with JIS B 0601.
[0016] As described above, the arithmetic surface roughness Ra of the surface of the second liner facing the second pressure-sensitive adhesive layer is 1 nm to 100 nm. The arithmetic surface roughness Ra of the surface of the first liner facing the first pressure-sensitive adhesive layer is preferably 1 nm to 60 nm, more preferably 1 nm to 45 nm, even more preferably 15 nm to 45 nm, and particularly preferably 25 nm to 45 nm. If within such a range, the above-mentioned effects of the present invention become prominent.
[0017] As described above, the maximum height Rz of the surface of the first liner on the first pressure-sensitive adhesive layer side is 5 nm to 1000 nm. The maximum height Rz of the surface of the first liner on the first pressure-sensitive adhesive layer side is preferably 10 nm to 800 nm, more preferably 30 nm to 600 nm, even more preferably 50 nm to 400 nm, and particularly preferably 50 nm to 200 nm. Within such a range, the effects of the present invention are prominent. The maximum height Rz can be measured in accordance with JIS B 0601.
[0018] As described above, the maximum height Rz of the surface of the second liner facing the second pressure-sensitive adhesive layer is 5 nm to 1000 nm. The maximum height Rz of the surface of the second liner facing the second pressure-sensitive adhesive layer is preferably 10 nm to 800 nm, more preferably 30 nm to 600 nm, even more preferably 50 nm to 500 nm, and particularly preferably 150 nm to 500 nm. If it is within such a range, the above-mentioned effects of the present invention become prominent.
[0019] The peel strength of the first liner from the double-sided adhesive sheet is preferably 0.001 N / 50 mm to 2 N / 50 mm, more preferably 0.01 N / 50 mm to 1.5 N / 50 mm, even more preferably 0.05 N / 50 mm to 1 N / 50 mm, and particularly preferably 0.1 N / 50 mm to 0.8 N / 50 mm. The peel strength of the first liner from the double-sided adhesive sheet (and the peel strength of the second liner from the double-sided adhesive sheet) refers to the adhesive strength measured by peeling the liner from the double-sided adhesive sheet of the liner-attached double-sided adhesive sheet (peel angle: 180°, peel speed (tensile speed): 300 mm / min) in an environment of 23° C. The peel strength of the liner from the double-sided adhesive sheet can be adjusted by any appropriate method, such as the composition of the adhesive layer, the type of liner, or the surface treatment applied to the liner.
[0020] The peel strength of the second liner from the double-sided pressure-sensitive adhesive sheet is preferably 0.001 N / 50 mm to 2 N / 50 mm, more preferably 0.01 N / 50 mm to 1.5 N / 50 mm, even more preferably 0.05 N / 50 mm to 1 N / 50 mm, and particularly preferably 0.1 N / 50 mm to 0.8 N / 50 mm. The peel strength of the first liner from the double-sided pressure-sensitive adhesive sheet and the peel strength of the second liner from the double-sided pressure-sensitive adhesive sheet may be the same or different.
[0021] The thickness of the first liner is preferably 5 μm to 250 μm, more preferably 10 μm to 200 μm, further preferably 20 μm to 150 μm, and most preferably 30 μm to 100 μm.
[0022] The thickness of the second liner is preferably 5 μm to 250 μm, more preferably 10 μm to 200 μm, further preferably 20 μm to 150 μm, and most preferably 30 μm to 100 μm. The thickness of the first liner and the thickness of the second liner may be the same or different.
[0023] The elastic modulus of the first liner (substantially the liner substrate) is 500 MPa to 5000 MPa, more preferably 500 MPa to 4000 MPa, and further preferably 700 MPa to 4000 MPa. In this specification, the elastic modulus refers to the elastic modulus measured by the nanoindentation method in an environment of 23°C. The elastic modulus measured by the nanoindentation method refers to the elastic modulus obtained by continuously measuring the load applied to the indenter and the indentation depth during loading and unloading when the indenter is pressed into a sample (which may be a liner substrate) and then obtaining an applied load-indentation depth curve. The conditions for measuring the elastic modulus by the nanoindentation method will be described later.
[0024] The elastic modulus of the second liner (substantially the liner substrate) is 500 MPa to 5000 MPa, more preferably 500 MPa to 4000 MPa, and further preferably 700 MPa to 4000 MPa. The elastic modulus of the first liner and the elastic modulus of the second liner may be the same or different.
[0025] The liner substrate may be made of any suitable material. The liner substrate may be, for example, a plastic film, a plastic sheet, or various sheet-like materials such as paper, cloth, nonwoven fabric, metal foil, or a plastic laminate thereof, or a laminate of plastics. Among them, plastic films and plastic sheets (hereinafter referred to as plastic films) are most preferable from the viewpoint of handling and cost. The material of the plastic film may be selected as necessary from the viewpoint of strength, heat resistance, etc. For example, olefin-based resins having α-olefin as a monomer component such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); polyvinyl chloride (PVC); polyphenylene sulfide (PPS); amide-based resins such as polyamide (nylon) and fully aromatic polyamide (aramid); polyether ether ketone (PEEK), polyimide, polyetherimide, polystyrene, and acrylic resins may be mentioned. Preferably, a liner substrate made of a polyester resin is used, and more preferably, a liner substrate made of polyethylene terephthalate is used. The above materials can be used alone or in combination of two or more. In addition, as the plastic film, any of unstretched films, uniaxially oriented films, and biaxially oriented films may be used. In addition, these films may be laminated films consisting of two or more film layers. In addition, from the viewpoint of adjusting the roughness on both sides and handling, a film to which a lubricant such as inert particles is appropriately added may be used. For example, inorganic fine particles made of antimony, silica gel, etc. may be used as the lubricant.
[0026] Any suitable treatment may be adopted as the treatment for forming the release treatment layer. In one embodiment, the release treatment layer is a silicone treatment layer. As the silicone, a reactive silicone compound whose main component is dimethylpolysiloxane and has a functional group required for crosslinking (curing) may be preferably used. This is because it can be applied to a film in a low molecular weight state, and can be cured after application to form a release treatment layer that is resistant to abrasion, etc. Examples of functional groups of reactive silicone compounds include vinyl groups, epoxy groups, alkoxy groups, and isocyanato groups.
[0027] The silicone-treated layer is formed, for example, by diluting the reactive silicone compound in a solvent or the like to adjust the concentration, and applying and heating the mixture using a gravure coater or the like. Heating promotes the drying of the solvent and the curing reaction. It is preferable to use a catalyst that promotes the curing reaction in combination. Examples of catalysts that can be used include complexes of metals such as platinum, palladium, rhodium, zirconium, and tin, organic bases such as amines, and organic acids such as acetic acid.
[0028] In one embodiment, the first liner and / or the second liner (substantially the release treatment layer of each liner) has a Si-Kα ray intensity by fluorescent X-ray analysis of 0.01 to 500 kcps (preferably 0.5 to 250 kcps, more preferably 1.0 to 150 kcps, even more preferably 1.05 to 100 kcps, and particularly preferably 5 to 100 kcps). Within such a range, the release treatment can be performed sufficiently and uniformly, and a liner with a favorably adjusted surface state can be obtained. The Si-Kα ray intensity by fluorescent X-ray analysis is a value obtained by measuring the Si intensity of the release treatment agent layer and the non-release treatment agent layer by fluorescent X-ray analysis, and subtracting the intensity of the non-release treatment agent layer from the intensity of the release treatment agent layer. The intensity can be adjusted by controlling the release treatment layer formation conditions, such as the application amount, concentration, application speed, and drying of the release treatment agent. It is preferable that the Si-Kα ray intensity of the first liner and the second liner are different. The difference in Si-Kα radiation intensity causes a difference in the releasability of the two liners, which can prevent undesirable properties in the use of the adhesive tape, such as the adhesive adhering to the liner side or the adhesive being torn off to the liner side when the liner is peeled off (the so-called tear-off phenomenon), and can further improve the uniformity of pressure application. The absolute value of the difference in Si-Kα radiation intensity between the first liner and the second liner is preferably 0.1 to 500, more preferably 0.1 to 200, even more preferably 0.1 to 150, and particularly preferably 1 to 80.
[0029] In one embodiment, the first liner and the second liner are different colors. A liner-attached double-sided pressure-sensitive adhesive sheet configured in this manner can be obtained, for example, by coloring one of the liners (for example, the liner substrate). If both liners are different colors, the front and back of the liner-attached double-sided pressure-sensitive adhesive sheet become clear, making it easy to identify the liner to be peeled off.
[0030] C. Double-sided adhesive sheet As described above, the double-sided pressure-sensitive adhesive sheet comprises a first pressure-sensitive adhesive layer, a substrate, and a second pressure-sensitive adhesive layer in this order. In one embodiment, the double-sided pressure-sensitive adhesive sheet further comprises an undercoat layer disposed between the second pressure-sensitive adhesive layer and the substrate. The undercoat layer makes it possible to obtain a double-sided pressure-sensitive adhesive sheet with excellent conformability to an adherend. When the second pressure-sensitive adhesive layer containing heat-expandable microspheres is heated, the heat-expandable microspheres expand, causing deformation in the thickness direction, but the undercoat layer suppresses deformation in the direction toward the substrate, improving peelability.
[0031] The adhesive strength at 23° C. when the first adhesive layer of the double-sided adhesive sheet is attached to polyethylene terephthalate is preferably 0.5 N / 20 mm or more, more preferably 0.5 N / 20 mm to 20 N / 20 mm, and even more preferably 0.5 N / 20 mm to 15 N / 20 mm. The adhesive strength refers to the adhesive strength measured by a method in accordance with JIS Z 0237:2000 (lamination conditions: one reciprocating motion with a 2 kg roller, peel speed: 300 mm / min, peel angle 180°).
[0032] The initial adhesive strength at 23°C when the second adhesive layer of the double-sided adhesive sheet is attached to polyethylene terephthalate is preferably 0.5 N / 20 mm or more, more preferably 0.5 N / 20 mm to 20 N / 20 mm, and even more preferably 0.5 N / 20 mm to 15 N / 20 mm. Within such ranges, a double-sided adhesive sheet useful as a temporary fixing sheet used in the manufacture of electronic components can be obtained. In this specification, the initial adhesive strength refers to the adhesive strength in a state where there is no decrease in adhesive strength due to the expansion of the heat-expandable microspheres, and means the adhesive strength in a state where there is no thermal history of 50°C or more.
[0033] The adhesive strength of the second adhesive layer of the double-sided adhesive sheet when attached to polyethylene terephthalate is preferably reduced to 0.2 N / 20 mm or less (preferably 0.1 N / 20 mm or less) by heating. The heating temperature is preferably 90°C to 300°C, more preferably 100°C to 280°C.
[0034] The thickness of the double-sided pressure-sensitive adhesive sheet is preferably 3 μm to 300 μm, more preferably 5 μm to 150 μm, and even more preferably 10 μm to 100 μm.
[0035] In one embodiment, at least one of the layers constituting the double-sided pressure-sensitive adhesive sheet is a colored layer. When there are multiple colored layers, it is preferable that each layer is a different color. With these configurations, the front and back of the liner-attached double-sided pressure-sensitive adhesive sheet are clearly distinguished, making it easy to identify the liner to be peeled off. Note that coloring refers to a state in which any or all light in the visible light region (250 nm to 700 nm) is absorbed and / or reflected. Any appropriate method can be used as a method for coloring any one layer.
[0036] As the colorant, a pigment or a dye can be used. As the pigment, for example, organic pigments include acrylic pigments, azo pigments, polyazo pigments, anthraquinone pigments, quinacridone pigments, isoindoline pigments, isoindolinone pigments, phthalocyanine pigments, perylene pigments, DPP pigments, fluorescent pigments, condensed polycyclic pigments, colored resin particles, etc., and inorganic pigments include known pigments such as carbon black, synthetic silica, chromium oxide, iron oxide, titanium oxide, zinc sulfide, calcined pigments, and natural mica. As the dye, acid dyes, reactive dyes, direct dyes, disperse dyes, cationic dyes, polymer dyes, etc. can be used. As the ink, a commercially available product such as "NB300" manufactured by Dainichi Seika Kagaku Co., Ltd. may be used. Note that coloring can also be achieved by mixing a colorant into the adhesive layer. In addition, when the composition of the adhesive layer has a fine structure of a size of about the visible light wavelength due to, for example, microphase separation between a hydrophilic composition and a hydrophobic composition, a phenomenon in which the coloring occurs according to the size, so-called structural color, may be exhibited, and coloring utilizing this phenomenon can also be used.
[0037] C-1. First adhesive layer The first adhesive layer is composed of any appropriate adhesive. Examples of adhesives constituting the first adhesive layer include acrylic adhesives, rubber adhesives, silicone adhesives, and the like. Among them, acrylic adhesives can be preferably used. Furthermore, an active energy ray curable acrylic adhesive (hereinafter, active energy ray curable adhesive) may be used as the adhesive. Details of the adhesive are described in, for example, JP 2015-168711 A. The description of this publication is incorporated herein by reference.
[0038] (Acrylic adhesive) In one embodiment, an acrylic adhesive is used as the adhesive. Examples of the acrylic adhesive include an acrylic adhesive having an acrylic polymer (homopolymer or copolymer) using one or more (meth)acrylic acid alkyl esters as a monomer component as a base polymer.
[0039] Specific examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and ) C1-20 alkyl esters of (meth)acrylic acid such as nonyl acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, preferred are (meth)acrylic acid alkyl esters having a linear or branched alkyl group having 4 to 20 carbon atoms (more preferably 6 to 20, particularly preferably 8 to 18), and more preferably 2-ethylhexyl (meth)acrylate.
[0040] The acrylic polymer may contain units corresponding to other monomer components copolymerizable with the alkyl (meth)acrylate, if necessary, for the purpose of modifying properties such as cohesive strength, heat resistance, and crosslinkability. Examples of such monomer components include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride monomers such as maleic anhydride and itanoic anhydride; hydroxyl group-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl methacrylate; sulfonic acid group-containing monomers such as styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; (N-substituted) amide monomers such as N,N-dimethyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; aminoalkyl(meth)acrylate monomers such as aminoethyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate, and t-butylaminoethyl(meth)acrylate; alkoxyalkyl(meth)acrylate monomers such as methoxyethyl(meth)acrylate and ethoxyethyl(meth)acrylate; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide;succinimide monomers such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyoctamethylene succinimide; vinyl monomers such as vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, and N-vinylcaprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, and methoxyethyl (meth)acrylate. glycol-based acrylic ester monomers such as ethylene glycol and methoxypolypropylene glycol (meth)acrylate; acrylic ester monomers having a heterocycle, a halogen atom, a silicon atom, or the like, such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, and silicone (meth)acrylate; polyfunctional monomers such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; olefin-based monomers such as isoprene, butadiene, and isobutylene;Examples of the monomer component include vinyl ether monomers such as vinyl ether. These monomer components may be used alone or in combination of two or more. Among the above, more preferred are carboxyl group-containing monomers (particularly preferably acrylic acid) or hydroxyl group-containing monomers (particularly preferably hydroxyethyl (meth)acrylate). The content of the structural unit derived from the carboxyl group-containing monomer is preferably 0.1% by weight to 10% by weight, more preferably 0.5% by weight to 5% by weight, and particularly preferably 1% by weight to 4% by weight, based on the total structural units constituting the acrylic polymer. The content of the structural unit derived from the hydroxyl group-containing monomer is preferably 0.1% by weight to 20% by weight, more preferably 0.5% by weight to 10% by weight, and particularly preferably 1% by weight to 7% by weight, based on the total structural units constituting the acrylic polymer. In this specification, (meth)acrylic means acrylic and / or methacrylic.
[0041] In one embodiment, the glass transition temperature (Tg) of the base polymer (e.g., acrylic polymer) is preferably −50° C. to 0° C., more preferably −40° C. to −5° C., and even more preferably −35° C. to −5° C. Within such a range, a pressure-sensitive adhesive layer having appropriate viscosity and capable of preventing displacement of the adherend when the adherend is pressed can be formed. In addition, a pressure-sensitive adhesive layer having excellent smoothness is formed, and damage to the adherend can be prevented. When the base polymer is a copolymer, the glass transition temperature is calculated by the Fox formula. The Fox formula is, as shown below, a relational expression between the glass transition temperature Tg (° C.) of the copolymer and the glass transition temperature Tgi (° C.) of a homopolymer (homopolymer) obtained by homopolymerizing each of the monomers (monomers) constituting the copolymer. In the following Fox formula, Tg (° C.) indicates the glass transition temperature of the copolymer, Wi indicates the weight fraction of the monomer i, and Tgi (° C.) indicates the glass transition temperature of the homopolymer formed from the monomer i. 1 / (273+Tg)=Σ(Wi / (273+Tgi)) The glass transition temperatures of the homopolymers formed from the monomers are as follows: acrylonitrile homopolymer (AN): 97°C, methyl methacrylate homopolymer (MMA): 102°C, methacryloylnitrile homopolymer (MAN): 120°C, vinylidene chloride homopolymer: 75°C, isobornyl acrylate homopolymer: 97°C, methyl acrylate homopolymer: 10°C, butyl acrylate homopolymer: -53°C, ethyl acrylate homopolymer: -23°C, acrylic acid homopolymer: 101°C, 2-ethylhexyl acrylate homopolymer: -52°C, and 2-hydroxyethyl acrylate: -14°C. In addition, the glass transition temperatures of the homopolymers other than these can be those described in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999). In addition, when multiple Tg values are described in this document, the "conventional" value is adopted. Furthermore, if no value is given in the aforementioned literature, the value given in https: / / polymerdatabase.com will be used, and if multiple Tg values are given, the "PREFERRED" value will be used.
[0042] The acrylic adhesive may contain any suitable additives as necessary, such as crosslinkers, tackifiers, plasticizers (e.g., trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers, etc.), pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, UV absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, etc.
[0043] Examples of the crosslinking agent contained in the acrylic adhesive include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, etc. Among these, isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred.
[0044] Specific examples of the isocyanate-based crosslinking agent contained in the acrylic adhesive include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate and xylylene diisocyanate; and isocyanate adducts such as trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HX"). The content of the isocyanate-based crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, and is typically 0.1 to 20 parts by weight, and more preferably 0.5 to 10 parts by weight, per 100 parts by weight of the base polymer.
[0045] Examples of the epoxy crosslinking agent contained in the acrylic adhesive include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Company, Inc., product name "Tetrad C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Company, Inc., product name "Epolite 1500NP"), ), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., product name "Epolight 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., product name "Epolight 70P"), polyethylene glycol diglycidyl ether (manufactured by Nippon Oil & Fats Co., Ltd., product name "Epiol E-400"), polypropylene glycol diglycidyl ether (manufactured by Nippon Oil & Fats Co., Ltd., product name "Epiol P-200"), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, product name "Denacol" Examples of the epoxy crosslinking agent include glycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-611"), glycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-314"), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation, trade name "Denacol EX-512"), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. The content of the epoxy crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, and is typically 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, relative to 100 parts by weight of the base polymer.
[0046] The thickness of the first pressure-sensitive adhesive layer is preferably 5 μm to 70 μm, more preferably 7 μm to 60 μm, even more preferably 15 μm to 55 μm, and most preferably 20 μm to 50 μm. Within such a range, a double-sided pressure-sensitive adhesive sheet can be obtained that is excellent in operability when peeling the liner, operability when applying, adhesiveness, smoothness, and deformability when heated.
[0047] The elastic modulus of the first pressure-sensitive adhesive layer is preferably 0.001 MPa to 10 MPa, and more preferably 0.01 MPa to 8 MPa. Within such a range, a double-sided pressure-sensitive adhesive sheet can be obtained that is excellent in operability in peeling the liner, operability in application, adhesiveness, smoothness, and deformability when heated. When the first pressure-sensitive adhesive layer contains an active energy ray-curable adhesive, the first pressure-sensitive adhesive layer is cured by irradiation with active energy rays, and the elastic modulus thereof is preferably 1 MPa to 200 MPa, more preferably 5 MPa to 150 MPa, and even more preferably 10 MPa to 100 MPa.
[0048] C-2. Second adhesive layer The second adhesive layer may contain any suitable adhesive and heat-expandable microspheres. Examples of the adhesive constituting the second adhesive layer include acrylic adhesives, rubber adhesives, silicone adhesives, and the like. Among them, acrylic adhesives may be preferably used. Furthermore, an active energy ray-curable acrylic adhesive (hereinafter, active energy ray-curable adhesive) may be used as the adhesive. Details of the adhesive are described in, for example, JP 2015-168711 A. The description of this publication is incorporated herein by reference.
[0049] The thickness of the second pressure-sensitive adhesive layer is preferably 1 μm to 60 μm, more preferably 2 μm to 50 μm, even more preferably 3 μm to 35 μm, and most preferably 5 μm to 35 μm. Within such a range, a double-sided pressure-sensitive adhesive sheet can be obtained that has excellent operability in peeling the liner, operability during application, adhesiveness, and smoothness.
[0050] The elastic modulus of the second pressure-sensitive adhesive layer is preferably 0.001 MPa to 10 MPa, and more preferably 0.01 MPa to 8 MPa. Within such a range, a double-sided pressure-sensitive adhesive sheet can be obtained that exhibits excellent operability in liner peeling, operability during application, adhesiveness, and smoothness.
[0051] In one embodiment, the second pressure-sensitive adhesive layer contains the acrylic pressure-sensitive adhesive described in Section C-1. As described above, the acrylic pressure-sensitive adhesive contains an acrylic polymer as a base polymer.
[0052] (thermal expandable microspheres) As the heat-expandable microspheres, any suitable heat-expandable microspheres can be used as long as they are microspheres that can expand or foam when heated. For example, the heat-expandable microspheres can be microspheres in which a substance that easily expands when heated (a volatile substance) is encapsulated in an elastic shell. Such heat-expandable microspheres can be produced by any suitable method, such as a coacervation method or an interfacial polymerization method.
[0053] The volatile substance contained in the shell is typically an organic solvent. Examples of the organic solvent include linear aliphatic hydrocarbons having 3 to 8 carbon atoms and fluorinated products thereof, branched aliphatic hydrocarbons having 3 to 8 carbon atoms and fluorinated products thereof, linear alicyclic hydrocarbons having 3 to 8 carbon atoms and fluorinated products thereof, ether compounds having a hydrocarbon group having 2 to 8 carbon atoms, or compounds in which a part of the hydrogen atoms of the hydrocarbon group is replaced by a fluorine atom. In one embodiment, the organic solvent is propane, cyclopropane, butane, cyclobutane, isobutane, pentane, cyclopentane, neopentane, isopentane, hexane, cyclohexane, 2-methylpentane, 2,2-dimethylbutane, heptane, cycloheptane, octane, cyclooctane, methylheptanes, trimethylpentanes, and other hydrocarbons composed only of hydrogen atoms and carbon atoms; hydrofluoroethers such as C3F7OCH3, C4F9OCH3, and C4F9OC2H5. These organic solvents may be used alone or in combination of two or more.
[0054] The boiling point of the organic solvent is preferably -50°C to 100°C, more preferably -20°C to 100°C. Within this range, heat-expandable microspheres can be obtained whose shells can expand well without being destroyed. If the boiling point of the organic solvent is too low, the operation for suppressing volatilization during the production of heat-expandable microspheres may become complicated. When two or more kinds of organic solvents (mixed solvents) are used, the "boiling point of the organic solvent" refers to the boiling point of the solvent with the largest weight ratio.
[0055] The content of the organic solvent is preferably 5% by weight to 35% by weight, more preferably 10% by weight to 30% by weight, based on the weight of the heat-expandable microspheres before heating. In this range, the heat-expandable microspheres are dispersed with high uniformity in the pressure-sensitive adhesive layer. If the content is less than 5% by weight, the heat-expandable microspheres are likely to be unevenly distributed on the surface of the pressure-sensitive adhesive layer during production of the pressure-sensitive adhesive layer due to low density, etc., and excessively large irregularities may occur on the surface of the pressure-sensitive adhesive layer after heating. If the content is more than 35% by weight, the density is high and the microspheres settle in the pressure-sensitive adhesive layer, and sufficient irregularities may not be formed on the surface of the pressure-sensitive adhesive layer even when heated, and the desired peelability may not be obtained, and adhesive residue may also occur.
[0056] Examples of materials constituting the shell include resins, glass, and metals. Among these, resins are preferred. Examples of resins constituting the shell include polymers composed of nitrile monomers such as acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethoxyacrylonitrile, and fumaronitrile; carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid; vinylidene chloride; vinyl acetate; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and β-carboxyethyl acrylate; styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; amide monomers such as acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide; and the like. The polymer composed of these monomers may be a homopolymer or a copolymer. Examples of the copolymer include vinylidene chloride-methyl methacrylate-acrylonitrile copolymer, methyl methacrylate-acrylonitrile-methacrylonitrile copolymer, methyl methacrylate-acrylonitrile copolymer, acrylonitrile-methacrylonitrile-itaconic acid copolymer, etc. The resin forming the shell may be a crosslinked body. The excluded free volume of the polymer can be adjusted by crosslinking, and thereby the diffusibility of the encapsulated volatile substance, the expandability of the shell, etc. can be controlled.
[0057] In one embodiment, the resin constituting the shell contains at least one selected from the group consisting of a structural unit derived from isobornyl acrylate, a structural unit derived from methacrylonitrile, a structural unit derived from acrylonitrile, a structural unit derived from methyl (meth)acrylate, a structural unit derived from vinylidene chloride, and a structural unit derived from (meth)acrylic acid. The resin having these structural units can be used to form a shell that has low solubility in the organic solvent contained therein and is difficult for the organic solvent to penetrate or infiltrate before heating. The resin can also be used to obtain heat-expandable microspheres that are excellent in deformability upon heating. Furthermore, the monomer can be used to easily control the thermal properties of the shell by crosslinking or the like. In one embodiment, methyl (meth)acrylate is preferably used from the viewpoint of ease of control of the shell hardness. The use of methyl (meth)acrylate can easily control the hardness of the shell by crosslinking, for example, by electron beam crosslinking or the like. When methyl (meth)acrylate is used, the content of the methyl (meth)acrylate is preferably less than 65 parts by weight, more preferably 1 to 55 parts by weight, and particularly preferably 1 to 50 parts by weight, relative to 100 parts by weight of the resin forming the shell. In addition, when flexibility is to be imparted to the shell, vinylidene chloride is preferably used. The amount of vinylidene chloride used can be any appropriate amount depending on the glass transition temperature of the desired resin.
[0058] The heat-expandable microspheres may be made of an inorganic or organic foaming agent, such as ammonium carbonate, ammonium hydrogen carbonate, sodium hydrogen carbonate, ammonium nitrite, sodium borohydride, and various azides. Examples of organic foaming agents include fluorinated alkane compounds such as trichloromonofluoromethane and dichloromonofluoromethane; azo compounds such as azobisisobutyronitrile, azodicarbonamide and barium azodicarboxylate; hydrazine compounds such as paratoluenesulfonylhydrazide, diphenylsulfone-3,3'-disulfonylhydrazide, 4,4'-oxybis(benzenesulfonylhydrazide) and allylbis(sulfonylhydrazide); semicarbazide compounds such as p-toluylenesulfonylsemicarbazide and 4,4'-oxybis(benzenesulfonylsemicarbazide); triazole compounds such as 5-morpholyl-1,2,3,4-thiatriazole; and N-nitroso compounds such as N,N'-dinitrosopentamethylenetetramine and N,N'-dimethyl-N,N'-dinitrosoterephthalamide.
[0059] The thickness of the shell is preferably 15 μm or less, more preferably 7 μm or less, even more preferably 5 μm or less, and particularly preferably 4 μm or less.
[0060] The glass transition temperature (Tg) of the resin constituting the shell is preferably 50°C to 250°C, more preferably 60°C to 200°C, and further preferably 80°C to 150°C.
[0061] The particle size of the heat-expandable microspheres before heating is preferably 0.5 μm to 80 μm, more preferably 5 μm to 45 μm, further preferably 10 μm to 20 μm, and particularly preferably 10 μm to 15 μm.
[0062] The volume cumulative particle diameter D50 (particle diameter at 50% cumulative volume) of the heat-expandable microspheres is preferably 5 μm to 30 μm, more preferably 7 μm to 24 μm. Within this range, a pressure-sensitive adhesive layer can be formed that has excellent releasability after heating while having excellent surface smoothness before heating. When a double-sided pressure-sensitive adhesive sheet having such a pressure-sensitive adhesive layer is used, the uniformity of the pressure applied can be improved when a member is pressed on the double-sided pressure-sensitive adhesive sheet. The volume cumulative particle diameters D50 and D80 (described later) are particle diameters before heating.
[0063] The volume-cumulative particle size D80 (particle size at 80% cumulative volume) of the heat-expandable microspheres is preferably 10 μm to 50 μm, more preferably 15 μm to 40 μm, and even more preferably 15 μm to 35 μm. Within this range, a double-sided pressure-sensitive adhesive sheet can be obtained that can improve the uniformity of pressure when a member is pressed on the double-sided pressure-sensitive adhesive sheet.
[0064] The inventors of the present invention have found that not only the surface condition of the first pressure-sensitive adhesive layer but also the surface condition of the second pressure-sensitive adhesive layer containing heat-expandable microspheres affects the uniformity of pressure applied to a workpiece placed on the first pressure-sensitive adhesive layer. By adjusting the volume-cumulative particle diameter D50 and / or D80 of the heat-expandable microspheres as described above, the surface condition of the second pressure-sensitive adhesive layer can be more appropriately controlled, and the above-mentioned effects of the present invention become more pronounced.
[0065] A group of heat-expandable microspheres having a desired particle size can be obtained by fractionation utilizing the difference in sedimentation speed in an air stream or liquid, fractionation by centrifugation, or fractionation using a sieve. In particular, pressure filtration using a resin filter is preferable from the viewpoint of industrial mass production even if the heat-expandable microspheres are dispersed in a solvent before being mixed with an adhesive or in an adhesive solution. As a filter system used for pressure filtration, for example, a system in which a filter is inserted into a pressure-resistant housing (e.g., NF-1P, manufactured by Chisso Filter Co., Ltd.) such as Kanefeel R series (Fuji Chemical Co., Ltd.) or Chisso CPII filter (manufactured by Chisso Filter Co., Ltd.) and a pump such as a diaphragm pump (e.g., AOD series pump, manufactured by Takato Technica Co., Ltd.) can be used, and the heat-expandable microparticles mixed in a solvent or adhesive solution can be classified by feeding the filter into the system. The mesh value of the filter is preferably 5 to 35 μm, more preferably 10 to 25 μm. If the mesh value exceeds 35 μm, the particle size distribution range of the heat-expandable microspheres will be wide, or the average particle size of the heat-expandable microspheres will exceed 30 μm, resulting in problems such as large irregularities in the heat-peelable adhesive layer. If the mesh size is less than 5 μm, the heat-expandable microspheres will be densely packed in the adhesive, leading to a decrease in the adhesive strength of the heat-peelable adhesive layer, or the expansion of the heat-expandable microspheres during heating will be small, resulting in a decrease in thermal peelability. Filtration may be performed only once, or multiple filters may be connected in series. In this specification, the average particle size and particle size distribution can be measured by the following method using X-ray CT of the adhesive layer before heating. i) The sample is fixed to a holder with the second adhesive layer facing up, and 1601 continuous transmission images are taken from 0 to 180° using an X-ray CT scanner. ii) A tomographic image was created by reconstruction based on the obtained total transmission image, and a three-dimensional reconstruction image (TIF stack image) and a reconstructed cross-sectional image (three-plane view) were created using analysis software. iii) The obtained three-dimensional reconstructed images (TIF stack images) were subjected to image processing to identify the heat-expandable microspheres. From the identification results, the volume of each heat-expandable microsphere was determined, and the sphere-equivalent diameter of each was calculated from the volume, from which the average particle size and particle size distribution were determined.
[0066] The heat-expandable microspheres preferably have an appropriate strength so that they do not burst until their volumetric expansion rate reaches at least 5 times, more preferably at least 7 times, and even more preferably at least 10 times. When such heat-expandable microspheres are used, their adhesive strength can be efficiently reduced by heat treatment.
[0067] The content of the heat-expandable microspheres in the pressure-sensitive adhesive layer can be appropriately set depending on the desired decrease in adhesive strength, etc. The content of the heat-expandable microspheres is, for example, 1 to 150 parts by weight, preferably 10 to 130 parts by weight, and more preferably 25 to 100 parts by weight, relative to 100 parts by weight of the base polymer forming the pressure-sensitive adhesive layer.
[0068] The arithmetic surface roughness Ra of the first pressure-sensitive adhesive layer before the heat-expandable microspheres expand (ie, before heating) is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less.
[0069] C-3. Undercoat layer The undercoat layer includes any appropriate adhesive. Examples of the adhesive constituting the undercoat layer include acrylic adhesives, rubber adhesives, silicone adhesives, and the like. Among them, acrylic adhesives can be preferably used. Furthermore, an active energy ray curable acrylic adhesive (hereinafter, active energy ray curable adhesive) may be used as the adhesive. Preferably, the adhesive constituting the undercoat layer is the same adhesive as the adhesive constituting the first adhesive layer.
[0070] The thickness of the undercoat layer is preferably 1 μm to 40 μm, more preferably 5 μm to 35 μm, and even more preferably 10 μm to 30 μm. Within such a range, a double-sided PSA sheet can be obtained that has excellent operability in peeling the liner and that suppresses the influence of the heat-expandable microspheres on the substrate side when heated.
[0071] The elastic modulus of the undercoat layer is preferably 0.001 MPa to 10 MPa, more preferably 0.01 MPa to 8 MPa, and more preferably 0.5 MPa to 5 MPa. Within such ranges, a double-sided pressure-sensitive adhesive sheet can be obtained that has excellent operability in peeling off the liner and suppresses the influence on the substrate side when the heat-expandable microspheres are heated. When the undercoat layer contains an active energy ray-curable pressure-sensitive adhesive, the undercoat layer is cured by irradiation with active energy rays, and the elastic modulus of the undercoat layer is preferably 1 MPa to 200 MPa, more preferably 5 MPa to 150 MPa, and even more preferably 10 MPa to 100 MPa.
[0072] C-4. Base material The substrate may be made of any suitable material. As the substrate, various sheet-like materials such as paper, cloth, nonwoven fabric, metal foil, plastic laminates thereof, and laminates of plastics can be used. Among them, plastic films and plastic sheets (hereinafter referred to as plastic films) are most preferable from the viewpoint of handling and cost. The material of the plastic film can be selected as necessary from the viewpoint of strength, heat resistance, and the like. For example, olefin-based resins having α-olefin as a monomer component such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); polyvinyl chloride (PVC); polyphenylene sulfide (PPS); amide-based resins such as polyamide (nylon) and fully aromatic polyamide (aramid); polyether ether ketone (PEEK), polyimide, polyetherimide, polystyrene, and acrylic resins can be mentioned. These materials can be used alone or in combination of two or more. The plastic film may be any of an unstretched film, a uniaxially oriented film, and a biaxially oriented film. These films may be laminated films consisting of two or more film layers, or from the viewpoint of handling, a film containing a lubricant such as inert particles may be appropriately added.
[0073] In one embodiment, the product of the cube of the thickness of the substrate and the elastic modulus of the substrate is preferably 1×10 -7 ( N m )~5×10 -2 ( N m ), more preferably 6×10 -6 ( N m )~3×10 -2 ( N m ), more preferably 2 × 10 -5 ( N m )~2.5×10 -2 ( N mWithin this range, it is possible to obtain a double-sided PSA sheet that is less likely to buckle when cut and has excellent cushioning properties.
[0074] The thickness of the substrate is preferably 20 μm to 250 μm, more preferably 30 μm to 200 μm, and even more preferably 35 μm to 190 μm. Within such ranges, a double-sided pressure-sensitive adhesive sheet excellent in strength, flexibility, suppleness, buckling resistance, operability, etc. can be obtained.
[0075] The elastic modulus of the substrate is preferably 500 MPa to 5000 MPa, more preferably 650 MPa to 4500 MPa, and even more preferably 750 MPa to 4000 MPa. Within such ranges, a double-sided pressure-sensitive adhesive sheet excellent in strength, flexibility, suppleness, buckling resistance, operability, etc. can be obtained.
[0076] The substrate may be subjected to a surface treatment, such as corona treatment, chromate treatment, ozone exposure, flame exposure, high-voltage shock exposure, ionizing radiation treatment, or coating with a primer.
[0077] In order to improve the visibility of the edge of the liner and to improve the anchoring of the base material and the adhesive layer, the base material may be printed with ink, etc. For ink, Dainichi Seika Chemical's "NB300" or the like can be used.
[0078] C-5. Manufacturing method of double-sided adhesive sheet The double-sided pressure-sensitive adhesive sheet can be produced by any suitable method. The double-sided pressure-sensitive adhesive sheet of the present invention can be obtained, for example, by a method in which a composition containing a pressure-sensitive adhesive is applied onto a liner to form a laminate (first liner / first pressure-sensitive adhesive layer, second pressure-sensitive adhesive layer / second liner) and the laminate is laminated onto a substrate. The composition containing a pressure-sensitive adhesive can contain any suitable solvent.
[0079] The second pressure-sensitive adhesive layer can be formed by coating a substrate with a composition containing heat-expandable microspheres, a pressure-sensitive adhesive, and any suitable solvent. Alternatively, the pressure-sensitive adhesive layer containing heat-expandable microspheres may be formed by sprinkling heat-expandable microspheres on the pressure-sensitive adhesive coating layer and then embedding the heat-expandable microspheres in the pressure-sensitive adhesive using a laminator or the like.
[0080] When the double-sided pressure-sensitive adhesive sheet has the above-mentioned undercoat layer, the undercoat layer can be formed, for example, by applying a composition for forming the undercoat layer (adhesive) onto the substrate or onto the second pressure-sensitive adhesive layer.
[0081] Any suitable coating method can be adopted as the coating method of the pressure-sensitive adhesive. For example, each layer can be formed by coating and then drying. Examples of the coating method include coating methods using a multi-coater, a die coater, a gravure coater, an applicator, etc. Examples of the drying method include natural drying, heat drying, etc. The heating temperature when heat drying can be set to any suitable temperature depending on the characteristics of the material to be dried.
[0082] D.Applications The liner-attached double-sided pressure-sensitive adhesive sheet can be preferably used as a temporary fixing sheet when processing any appropriate member (e.g., electronic components such as semiconductor chips). In one embodiment, the liner-attached double-sided pressure-sensitive adhesive sheet can be used as a sheet for temporarily fixing a semiconductor chip when manufacturing a CSP (Chip Size / Scale Package) or a WLP (Wafer Level Package). In one embodiment, the liner-attached double-sided pressure-sensitive adhesive sheet is used in processing including a step in which the second liner is peeled off first. In one embodiment, the semiconductor chip is pressure-processed.
[0083] In one embodiment, the liner-attached double-sided PSA sheet is in a roll form. EXAMPLES
[0084] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0085] [Production Example 1] Production of Liner a An addition type silicone treatment agent (manufactured by Shin-Etsu Silicones, main agent "KS-774": 100 parts by weight, catalyst "CAT PL-3": 0.4 parts by weight) was dissolved in a mixed solvent of heptane and hexane (mixture weight ratio 1:1) to prepare a stripping treatment agent solution with the treatment agent concentration adjusted to 0.3%. Next, the release agent solution was applied to one side of a PET film (manufactured by Toray Industries, product name "Lumirror S10", thickness 38 μm) using the gravure method, and dried in a hot air oven to obtain a liner a with a thickness of 38 μm. The Si-Kα radiation intensity of the obtained liner was 8 (kcps) (the measurement method will be described later).
[0086] [Production Example 2] Production of Liner B An addition type silicone treatment agent (manufactured by Shin-Etsu Silicones, main agent "KS-774": 100 parts by weight, catalyst "CAT PL-3": 0.4 parts by weight) was dissolved in a mixed solvent of heptane and hexane (mixture weight ratio 1:1) to prepare a stripping treatment agent solution with the treatment agent concentration adjusted to 1.8%. Next, the release agent solution was applied to one side of a PET film (manufactured by Toray Industries, product name "Lumirror S10", thickness 38 μm) using the gravure method, and dried in a hot air oven to obtain a liner b with a thickness of 38 μm. The Si-Kα radiation intensity of the obtained liner was 84 (kcps).
[0087] [Production Example 3] Production of Liner C One side of a PET film (manufactured by Toray Industries, product name "Lumirror S10", thickness 38 μm) was sandblasted using a Sony "Powder Beam". An addition type silicone treatment agent (manufactured by Shin-Etsu Silicones, main agent "KS-774": 100 parts by weight, catalyst "CAT PL-3": 0.4 parts by weight) was dissolved in a mixed solvent of heptane and hexane (mixture weight ratio 1:1) to prepare a stripping treatment agent solution with the treatment agent concentration adjusted to 0.3%. Next, the above-mentioned release agent solution was applied to the sandblasted surface of the PET film by gravure coating, and then dried in a hot air oven to obtain a 38 μm-thick liner c. The Si-Kα radiation intensity of the obtained liner was 18 (kcps).
[0088] [Production Example 4] Production of Liner D One side of a PET film (manufactured by Toray Industries, product name "Lumirror S10", thickness 38 μm) was sandblasted using a Sony "Powder Beam". An addition type silicone treatment agent (manufactured by Shin-Etsu Silicones, main agent "KS-774": 100 parts by weight, catalyst "CAT PL-3": 0.4 parts by weight) was dissolved in a mixed solvent of heptane and hexane (mixture weight ratio 1:1) to prepare a stripping treatment agent solution with the treatment agent concentration adjusted to 1.8%. Next, the above-mentioned release agent solution was applied to the sandblasted surface of the PET film by gravure coating, and then dried in a hot air oven to obtain a 38 μm-thick liner d. The Si-Kα radiation intensity of the obtained liner was 184 (kcps).
[0089] [Production Example 5] Production of Base Polymer 1 70 parts of ethyl acrylate, 3 parts of butyl acrylate, 30 parts of 2-ethylhexyl acrylate, 5 parts of methyl methacrylate, 3.5 parts of 2-hydroxyethyl acrylate, and 0.2 parts of benzoyl peroxide as a polymerization initiator were added to toluene, and then heated to obtain a toluene solution of an acrylic copolymer (acrylic polymer 1). Note that 3.1% by weight of the repeating units derived from the monomers constituting the acrylic polymer 1 are repeating units derived from the monomers having an active hydrogen group. The Tg of the acrylic polymer 1 is -31°C.
[0090] [Production Example 6] Production of base polymer 2 50 parts of butyl acrylate, 50 parts of ethyl acrylate, 5 parts of acrylic acid, 0.2 parts of 2-hydroxyethyl acrylate, and 0.2 parts of benzoyl peroxide as a polymerization initiator were added to toluene, and the mixture was heated to obtain a toluene solution of an acrylic copolymer (acrylic polymer 2). Of the repeating units derived from monomers constituting the acrylic polymer 2, 4.9% by weight is a repeating unit derived from a monomer having an active hydrogen group. The Tg of the acrylic polymer 2 is -35°C.
[0091] [Production Example 7] Production of base polymer 3 70 parts of methyl acrylate, 2 parts of butyl acrylate, 30 parts of 2-ethylhexyl acrylate, 10 parts of acrylic acid, and 0.2 parts of benzoyl peroxide as a polymerization initiator were added to ethyl acetate, and the mixture was heated to obtain an ethyl acetate solution of an acrylic copolymer (acrylic polymer 3). Of the repeating units derived from the monomers constituting acrylic polymer 3, 8.9% by weight is a repeating unit derived from a monomer having an active hydrogen group. The Tg of the acrylic polymer 3 is -6°C.
[0092] [Example 1] (Preparation of First Liner / First Pressure-Sensitive Adhesive Layer / Base Material Laminate) A mixed solution A was prepared by mixing a toluene solution of polymer 1 (1:100 parts acrylic polymer), 3 parts of an isocyanate-based crosslinking agent (manufactured by Nippon Polyurethane Co., Ltd., product name "Coronate L"), and 10 parts of a plasticizer (manufactured by DIC Corporation, product name "Monocizer W700"). Mixture A was applied to the release treatment agent-coated surface of liner a to form a 7 μm-thick adhesive layer, thereby obtaining a laminate consisting of a first liner / first adhesive layer. Furthermore, a substrate (oriented polypropylene film (OPP film), manufactured by Toray Industries, product name "Treyfan", thickness: 38 μm) was bonded to the surface of the first adhesive layer of the first liner / first adhesive layer laminate to obtain a laminate consisting of the first liner / first adhesive layer / substrate. (Preparation of First Liner / First Pressure-Sensitive Adhesive Layer / Substrate / Undercoat Layer Laminate) A mixed solution B was prepared by mixing a toluene solution of polymer 1 (polymer 1:100 parts) and 3 parts of an isocyanate-based crosslinking agent (manufactured by Nippon Polyurethane Industries, Ltd., product name "Coronate L"). A PET film that had been subjected to a silicone-based release treatment was coated with mixed solution B to form an undercoat layer having a thickness of 13 μm. The undercoat layer was transferred to the substrate surface of a first liner / first adhesive layer / substrate laminate to obtain a laminate consisting of a first liner / first adhesive layer / substrate / undercoat layer. (Preparation of Second Adhesive Layer / Second Liner) A toluene solution of polymer 1 (polymer 1:100 parts), 1.5 parts of an isocyanate-based crosslinking agent (manufactured by Nippon Polyurethane Co., Ltd., product name "Coronate L"), 10 parts of a tackifying resin (manufactured by Sumitomo Bakelite Co., Ltd., product name "Sumilite PR12603"), 30 parts of thermally expandable microspheres (manufactured by Matsumoto Yushi Pharmaceutical Co., Ltd., product name "Matsumoto Microsphere FN-180SSD"), and 0.5 parts of a colorant (manufactured by Dainichiseika Chemicals Co., Ltd., product name "DYMICS SZ-7510 Green") were mixed together to prepare mixed solution C. The mixed liquid C was applied to the release treatment agent-coated surface of the liner b to form a 35 μm-thick adhesive layer, thereby obtaining a laminate consisting of a second adhesive layer / second liner. (Preparation of double-sided adhesive sheet with liner) The first liner / first adhesive layer / substrate / undercoat layer laminate and the second adhesive layer / second liner were bonded together with the undercoat layer facing the second adhesive layer to obtain a liner-attached double-sided adhesive sheet (first liner / double-sided adhesive sheet (first adhesive layer / substrate / undercoat layer / second adhesive layer) / second liner).
[0093] [Example 2] A liner-attached double-sided adhesive sheet was obtained in the same manner as in Example 1, except that a substrate (PET film, manufactured by Toray Industries, Inc., product name "Lumirror S10", thickness: 75 μm) was used instead of the substrate (stretched polypropylene film (OPP film), manufactured by Toray Industries, Inc., product name "Treyfan", thickness: 38 μm).
[0094] [Example 3] A liner-attached double-sided adhesive sheet was obtained in the same manner as in Example 1, except that a substrate (PET film, manufactured by Toray Industries, Inc., product name "Lumirror S10", thickness: 188 μm) was used instead of the substrate (oriented polypropylene film (OPP film), manufactured by Toray Industries, Inc., product name "Treyfan", thickness: 38 μm).
[0095] [Example 4] A liner-attached double-sided PSA sheet was obtained in the same manner as in Example 1, except that Matsumoto Yushi Pharmaceutical Co., Ltd.'s product name "Matsumoto Microsphere FN-180SSD" was fed into a centrifugal air classifier and the heat-expandable microspheres were classified to have a D50 of 7 μm and a D80 of 15 μm.
[0096] [Example 5] A liner-attached double-sided PSA sheet was obtained in the same manner as in Example 1, except that Matsumoto Yushi Pharmaceutical Co., Ltd.'s product name "Matsumoto Microsphere FN-180SSD" was fed into a centrifugal air classifier and the heat-expandable microspheres were classified to have a D50 of 28 μm and a D80 of 45 μm.
[0097] [Example 6] A mixed solution A' was prepared by mixing a toluene solution of polymer 2 (100 parts of acrylic polymer 2), 0.8 parts of an epoxy-based crosslinking agent (manufactured by Mitsubishi Gas Corporation, product name "Tetrad C"), and 5 parts of a tackifier (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Polystar S145"). A liner-attached double-sided PSA sheet was obtained in the same manner as in Example 1, except that mixed liquid A' was used instead of mixed liquid A to form a first PSA layer having a thickness of 5 μm.
[0098] [Example 7] A mixed solution A'' was prepared by mixing a toluene solution of polymer 3 (100 parts of acrylic polymer 3), 1.2 parts of an epoxy-based crosslinking agent (manufactured by Mitsubishi Gas Corporation, product name "Tetrad C"), and 5 parts of a tackifier (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Polystar S145"). A liner-attached double-sided PSA sheet was obtained in the same manner as in Example 1, except that mixed liquid A″ was used instead of mixed liquid A to form a first PSA layer having a thickness of 5 μm.
[0099] [Comparative Example 1] A liner-attached double-sided PSA sheet was obtained in the same manner as in Example 1, except that liner c was used instead of liner a, and Matsumoto Yushi Pharmaceutical Co., Ltd.'s product name "Matsumoto Microsphere FN-180D" was used as the heat-expandable microspheres.
[0100] [Comparative Example 2] A liner-attached double-sided PSA sheet was obtained in the same manner as in Example 1, except that liner d was used instead of liner a, and Matsumoto Yushi Pharmaceutical Co., Ltd.'s product name "Matsumoto Microsphere FN-180D" was used as the heat-expandable microspheres.
[0101] [evaluation] The liner-attached double-sided PSA sheets obtained in the Examples and Comparative Examples were subjected to the following evaluations, and the results are shown in Table 1. (1) Arithmetic surface roughness Ra, maximum height Rz The arithmetic surface roughness Ra and maximum height Rz of the release treatment agent-coated surfaces of the first liner and the second liner (i.e., the surfaces on the adhesive layer side) were measured in accordance with JIS B 0601 using an optical surface roughness meter (manufactured by Veeco Metrology Group, product name "Wyko NT9100"). (2) Volume cumulative particle size D50, D80 of heat-expandable microspheres The volume cumulative particle diameter D50 of the heat-expandable microspheres was measured using X-ray CT by the following method. i) The sample was fixed in a holder with the second adhesive layer facing up, and 1601 continuous transmission images were taken from 0 to 180° using an X-ray CT scanner, Xradia 520 Versa, ZEISS, at a tube voltage of 40 kV, a tube current of 73 μA, and a pixel size of 0.3 μm / Pixel. ii) Based on the total transmission image obtained, reconstruction was performed to create a tomographic image, and a three-dimensional reconstruction image (TIF stack image) and a reconstructed cross-sectional image (three-plane view) were created using the analysis software ImageJ. iii) The obtained three-dimensional reconstructed images (TIF stack images) were subjected to image processing to identify the heat-expandable microspheres. From the identification results, the volume of each heat-expandable microsphere was determined, and the sphere-equivalent diameter of each was calculated from the volume, from which the volume-accumulated particle diameters D50 and D80 of the heat-expandable microspheres were determined. (3) Elastic modulus The elastic modulus was obtained by pressing a probe (indenter) against the object to be measured (substrate) and numerically processing the displacement-load hysteresis curve using software (triboscan) provided with the measuring device (average value of three measurements). The nanoindenter device and measurement conditions are as follows. Apparatus and measurement conditions: Nanoindenter; Triboindenter manufactured by Hysitron Inc. Measurement method: Single indentation method ·Measurement temperature: 25℃ Push-in speed: approx. 1000nm / sec Indentation depth: approx. 800 nm Probe: Diamond, Berkovich type (triangular pyramid type) (4) Evaluation of the adhesive layer surface shape The surface shape of the first adhesive layer was formed on a UV-curable adhesive tape (manufactured by Nitto Denko Corporation, product name "UB-3102D"), and the surface shape of the first adhesive layer was evaluated. Specifically, the evaluation was performed by the following method. The liner of the liner-attached double-sided pressure-sensitive adhesive sheet was peeled off, the second pressure-sensitive adhesive layer was attached to a glass plate, and a UV-curable pressure-sensitive adhesive tape (manufactured by Nitto Denko Corporation, product name "UB-3102D") was attached to the first pressure-sensitive adhesive layer. Thereafter, the adhesive surface of the UV-curable adhesive tape was cured. The curing was performed by applying ultraviolet light (irradiation dose 460 mJ / cm) using an ultraviolet irradiation device (UM-810 manufactured by Nitto Seiki Co., Ltd.). 2 ) was irradiated from the substrate side of UB-3102D. Next, the UV-curable adhesive tape was peeled off, and the maximum peak height Rp of the surface that had been attached to the first adhesive layer was measured. Tapes with a maximum peak height Rp of 3 μm or less were evaluated as passing (◯ in the table). The smoother the surface shape of the pressure-sensitive adhesive layer evaluated by this procedure, the more uniform the pressure can be applied when a member is pressed onto the double-sided pressure-sensitive adhesive sheet. (5) Measurement of Si-Kα line intensity of liner X-ray fluorescence analysis was performed on 100 points randomly selected on the liner surface (release-treated surface). More specifically, the Si-Kα radiation intensity (i) of the surface of the liner in contact with the adhesive layer (the surface coated with a release agent) and the Si-Kα radiation intensity (ii) of the surface not in contact with the adhesive layer (the surface not coated with a release agent) were measured, the absolute value of the value obtained by subtracting the value of (ii) from the value of (i) was calculated, and the average value of the 100 points was taken as the Si-Kα radiation intensity of the liner. The Si-Kα radiation intensity is the intensity at a wavelength of 7.125 angstroms measured using the following device. Equipment: Rigaku ZSX100e Analysis area: 30mmφ Analysis element: Si Analytical crystal: RX4 Output: 50kV, 70mA
[0102] [Table 1] [Explanation of symbols]
[0103] 10 First Liner 20 Double-sided adhesive sheet 21 First adhesive layer 22 Base material 23 Second adhesive layer 30 The Second Diner 100 Adhesive Sheet
Claims
1. a first liner, a first pressure-sensitive adhesive layer, a substrate, a second pressure-sensitive adhesive layer, and a second liner, in this order; the second pressure-sensitive adhesive layer contains heat-expandable microspheres, the arithmetic surface roughness Ra of the surface of the first liner facing the first pressure-sensitive adhesive layer is 1 nm to 100 nm; the arithmetic surface roughness Ra of the surface of the second liner facing the second PSA layer is 1 nm to 100 nm; the maximum height Rz of the surface of the first liner facing the first pressure-sensitive adhesive layer is 5 nm to 1000 nm; the maximum height Rz of the surface of the second liner facing the second PSA layer is 5 nm to 1000 nm; The heat-expandable microspheres have a volume cumulative particle diameter D50 of 5 μm to 30 μm; The heat-expandable microspheres have a volume cumulative particle diameter D80 of 10 μm to 50 μm. the absolute value of the difference in Si-Kα ray intensity between the first liner and the second liner as determined by fluorescent X-ray analysis is 0.1 to 500 kcps; Double-sided adhesive sheet with liner.
2. The product of the cube of the thickness of the substrate and the elastic modulus of the substrate is 1×10 -7 (N.m) to 1 x 10 -2 2. The liner-attached double-sided pressure-sensitive adhesive sheet according to claim 1, wherein the tension is 1.0 N·m.
3. the first pressure-sensitive adhesive layer is made of a pressure-sensitive adhesive containing a base polymer, 3. The liner-attached double-sided pressure-sensitive adhesive sheet according to claim 1, wherein the base polymer has a glass transition temperature of -50°C to 0°C.
4. 4. The liner-attached double-sided pressure-sensitive adhesive sheet according to claim 1, which is used as a sheet for temporarily fixing a semiconductor chip during the manufacture of a CSP (Chip Size / Scale Package).
5. 4. The liner-attached double-sided pressure-sensitive adhesive sheet according to claim 1, which is used as a sheet for temporarily fixing a semiconductor chip during the manufacture of a WLP (wafer level package).
6. The liner-attached double-sided pressure-sensitive adhesive sheet according to claim 4 or 5, wherein the semiconductor chip is subjected to pressure processing.
Citation Information
Patent Citations
Method for manufacturing heat separation-type adhesive sheet
JP2002220569A
Pressure-sensitive adhesive sheet with separator, assembly of optical member and method for assembling the same
JP2003201452A
Method of cutting electronic part
JP2006152308A
Method for processing adherend using thermally releasable pressure-sensitive adhesive sheet
JP2009035609A
Adhesive sheet
JP2021006635A